THE ROLE OF ORAL SPEECH DEVELOPMENT IN THE LANGUAGE (American Journal of Pedagogical and Educational Research, 2023)
Oral language development involves more than learning words. It also entails the development of speech skills that enable children to express themselves clearly and effectively. Verbal expression gives way to creative communication, which also boosts self-esteem. Communication is the act of interacting and exchanging ideas with other people. Basically, when communicating, people send and receive messages. There are two primary forms of communication: verbal and nonverbal. With verbal communication, people express their thoughts, ideas, and feelings through spoken or written language. Nonverbal communication uses other methods, such as body language including facial expressions, gestures, and other body movements. We are going to discuss both of these forms of communication and give verbal and nonverbal communication examples to help you understand them better so as to improve your information transfer.